Creatively teach the common core literacy standards with technology grades 6-12 - Tucker, Catlin R. (Corwin, 2016)
Tucker helps make the transition to the Common Core easier, by introducing to the technology and devices that will help you-- and your students-- create a more meaningful and resonant learning experience.